CHALLENGES OF NEWLY CREATED DISTRICTS IN GHANA: A CASE STUDY OF THE ASANTE AKIM NORTH DISTRICT - Mensah, John Victor; Adamtey, Ronald; Mohammed, Abdul-Wadudu Adam (Advances in Social Sciences Research Journal, 2015)
In an effort to bring governance to the doorstep of the people, promote participation in development, provide the citizenry with better conditions of living through better service delivery at the local level, many countries decentralize power and resources to the lower levels through the creation of new districts. Although this is laudable, existing studies do not adequately explain the challenges faced by newly created districts and how these can be overcome. Questionnaires and interview guides were used to interact with 54 high profile officers selected from the administration of the District Assembly, decentralized departments of the Assembly, Town Councils and Unit Committees of the Asante Akim North District to explore the challenges they face. It was revealed that the newly created district faces challenges in the delivery of their mandate. The challenges included incomplete institutional setup, inadequate human resources of key departments, weak logistical capacity, weak financial resource capacity, and poor management of built and natural environments. It is recommended that for newly created District Assemblies to effectively deliver their mandate, the exercise should adopt a comprehensive approach where all key departments are established and made functional. The Ministry of Local Government and Rural Development and other relevant ministries should regularly build the capacity of these institutions to make them effective at all times. The newly created district should have its financial resilience built to ensure adequate financial resources for undertaking development programs and projects.